Research on Ethernet-based Train Control Technology for Urban Railway System - Yishan LIU (机车电传动)
According to the practical application project of the new urban rail train, this paper made customized design and application demonstration of Ethernet control vehicle from the aspects of multi service bearing, reliability and safety. The actual operation results show that the designed system has significant advantages over the existing urban rail transit in terms of safety, stability, efficient operation and maintenance, which provides the basic support for the continuous development of urban rail transit.